Pengaruh Pengembangan Karir dan Kompensasi Terhadap Kinerja Karyawan dengan Disiplin Kerja Sebagai Variabel Intervening Pada PT. Kemilau Permata Sawit - Vito Anggara; Vivi Nila Sari; Nia Nadila (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to examine the influence of career development and compensation on employee performance, with work discipline as an intervening variable at PT. Kemilau Permata Sawit. Data collection methods included a survey and questionnaire distribution, with a sample of 74 respondents. The analysis method used was structural equation modeling using SmartPLS. The results showed a significant effect of career development on work discipline. There was a significant effect of compensation on work discipline. There was a significant effect of career development on employee performance. There was an insignificant effect of compensation on employee performance. There was a significant effect of work discipline on employee performance. Work discipline mediated the effect of career development on employee performance. Work discipline mediated the effect of compensation on employee performance.